2020
DOI: 10.1016/j.thromres.2020.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in patients with COVID-19: Systematic review and meta-analysis

Abstract: Background Venous thromboembolism (VTE) may complicate the course of Coronavirus Disease 2019 (COVID-19). Objectives To evaluate the incidence of VTE in patients with COVID-19. Methods MEDLINE, EMBASE, and PubMed were searched up to 24th June 2020 for studies that evaluated the incidence of VTE, including pulmonary embolism (PE) and/or deep vein thrombosis (DVT), in patients with COVID-19. Pooled proportions with corresponding 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
198
5
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(227 citation statements)
references
References 47 publications
16
198
5
8
Order By: Relevance
“…The incidence of VTE has increased in patients admitted for Covid-19, and further imaging may be recommended for low suspicion of VTE [5] .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of VTE has increased in patients admitted for Covid-19, and further imaging may be recommended for low suspicion of VTE [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Commonly recognised systemic venous thrombotic states in COVID-19 pneumonia are deep vein thrombosis and extensive pulmonary thromboembolism. 39 , 40 This venous-centred thrombosis seems to be very common in patients with severe COVID-19 who are on ventilators in intensive care. 41 …”
Section: Systemic Arterial and Venous Thromboembolism In Severe Covidmentioning
confidence: 99%
“…21 These results were matching to a recent meta-analysis that investigated the risk of VTE in COVID-19 patients found that the incidence of VTE is 26%, while DVT and PE were 12% and 14%, respectively. 22 A study that investigated patients from 2 leading hospitals in Wuhan, China found that out of 184 ICU patients, just more than a courter (27%) developed VTE, while less than 5% of patients developed arterial Thromboembolism (TE). 5 In the same line, Middeldorp et al 23 showed DVT has been formed in the same percentage (27%) of ICU and 1.6% of non-ICU patients with COVID-19.…”
Section: Prevalence and Incidence Of Vte In Covid-19 Patientsmentioning
confidence: 99%